Pneumatic Lock for Manhole and Bottom Loader on Fuel Tank Trucks: A Cloud-Based Digital Interlock System for Secure and Sustainable Fuel Distribution - Alvian Pratama; Saiful Hamzah; Ahmed Syarif; Giyarto Giyarto; Muhammad Wisnu Cakrawiguna (International Journal Labs, 2026)
Fuel distribution through road tank trucks plays a crucial role in downstream petroleum supply chains; however, it remains highly vulnerable to fuel theft, adulteration, and unauthorized access during transportation. Conventional mechanical sealing systems applied to manholes and bottom loading valves are widely recognized as weak security measures due to their susceptibility to manipulation and lack of digital traceability. These limitations result in transport losses, safety incidents, customer disputes, and regulatory non-compliance. This study presents the design, implementation, and performance evaluation of a Pneumatic Manhole Lock (P-Man) integrated with a digital spool lock and cloud-based interlock system for fuel tank trucks. The proposed solution combines physical pneumatic locking mechanisms with geofencing, one-time password (OTP) authentication, and real-time digital audit trails. Access to fuel compartments is strictly restricted to authorized locations and verified users, ensuring that opening actions can only occur at designated fuel stations. The system was implemented and tested on operational fuel tank trucks with multiple compartment configurations. Field results demonstrate a 77% reduction in sealing and verification time, complete prevention of unauthorized valve opening outside geofenced areas, significant reduction in transport loss, and a substantial increase in customer satisfaction from 42% to 93%. In addition, the system enhances safety performance and strengthens governance through transparent, auditable distribution records. The findings indicate that integrating pneumatic interlock systems with digital authorization provides a robust, scalable, and sustainable solution for improving fuel distribution security, operational efficiency, and regulatory compliance.